(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Mycotoxins are harmful secondary metabolites generated by a variety of fungi, and they may be found in a vast array of food and feed commodities and processed meats from animals fed infected meal. Numerous mycotoxins are extremely resistant and survive food processing, entering the food chain and posing a concern to human health. The "optical waveguide lightmode spectroscopy" (OWLS) method was used to detect aflatoxin B1 in plant sample matrices. The calibration curve for the detection of aflatoxin B1 utilizing "optical waveguide lightmode spectroscopy" (OWLS) displayed a sigmoidal shape; hence, the 5-PL or 4-PL model should be used to fit the data rather than a linear model. Using error function analysis with functions such as AICc, HQC, BIC, RMSE, adjR2, Bias Factor, and Accuracy Factor, the 5-PL and 4-Pl models are distinguished inconsistently. The overlapping confidence intervals of the LogEC50 values suggested that the two techniques did not differ much, and the 4-PL model was selected due to its smaller number of parameters. The Limits of Detection for aflatoxin B1 value based on the 4-PL equation was 8.787 ng/mL with the 95% confidence interval from 5.728 to 13.100. In this study, the use of the 4-PL model was successful and was able to represent the entire date curve, not only the linear section. The linear component is crucial as a handy and swift approach for assessing the sensitivity of a developed biosensor technology and is often a more beneficial method for field applications when a quick and straightforward evaluation is required.